Early predictors of lung necrosis severity in children with community‐acquired necrotizing pneumonia. Issue 9 (20th June 2022) - Li, Qiaoling; Zhang, Xueya; Chen, Bo; Ji, Yongan; Chen, Wei; Cai, Shujing; Xu, Ming; Yu, Mingwei; Bao, Qiyu; Li, Changchong; Zhang, Hailin
Abstract: Objective: To analyze baseline clinical and laboratory characteristics and explore the possible predictors of lung necrosis severity in children with community‐acquired necrotizing pneumonia (NP). Methodology: This retrospective observational study was performed in a tertiary referral center. A total of 104 patients aged <15 years with community‐acquired pneumonia and radiologically confirmed NP by computed tomography (CT) were included. Patients were classified into the mild, moderate, or massive necrosis groups. Results: Among them, 29, 41, and 34 patients had mild, moderate, and massive necrosis, respectively. Moreover, 34.6% of the patients were admitted to pediatric intensive care unit. Massive necrosis was more likely to occur during winter ( p < 0.05) and was associated with more severe clinical outcomes, such as longer duration of fever, longer hospitalization, increased mortality, and a higher risk of subsequent surgical intervention ( p < 0.05). Multivariate analysis demonstrated that the following were independent risk factors for massive necrosis in this study: C‐reactive protein (CRP) ( p = 0.036), serum albumin ( p = 0.009), and immunoglobulin M (IgM) ( p = 0.022). Receiver operating characteristic analysis showed that when the cut‐off value for CRP, serum albumin, and IgM were set at 122 mg/L, 30.8 g/L, and 95.7 mg/dl, respectively, they showed good diagnostic performance for differentiating patients with massive necrosis from all patients with NP. Conclusion: NP is a potentially severe complication of pediatric community‐acquired pneumonia. Different severities of lung necrosis can lead to different clinical outcomes. CRP, serum albumin, and IgM levels are independent predictors of the degree of lung necrosis.